A simple and novel marking method for correctly identifying the precutting direction to achieve safe and efficacious precut sphincterotomy (with video) - Nagai, Kazumasa (Endosc Int Open, 2019)
Background and study aims  Failure to recognize the right direction and precise incision length during precutting has been reported. To address these concerns, we developed a marking method that places a marking on the cutting endpoint before starting precutting. This preliminary study aimed to assess the effectiveness and safety of precut sphincterotomy using our new marking method. Patients and methods  Between April 2015 and May 2017, 21 patients from our tertiary referral center were included in this study. Precut sphincterotomy using our marking method was employed for difficult common bile duct cannulation cases. Before starting precutting, a marking was placed slightly before the upper margin of the bulge of the papilla in the 11- to 12-o’clock direction as a cutting endpoint by cauterization with a needle knife. Results  Technical success was obtained in all 21 procedures. There were no post-endoscopic retrograde cholangiopancreatography (ERCP) complications except for one mild case of post-ERCP pancreatitis. Conclusion  Our new marking method before precutting enabled precise incision and quick bile duct cannulation without causing severe complications.